Effects of air curtain dust control parameters on dust pollution in fully mechanized mining faces - LI Changjie; XIN Chuangye; WANG Hao (Gong-kuang zidonghua)
The effectiveness of air curtain dust control is influenced by various factors, including suction ventilation and radial airflow distribution. Existing research is largely limited to the effects of single factors on air curtain dust control. To understand the impact of dust control parameters on dust pollution in fully mechanized mining faces, numerical simulations were conducted to investigate the evolution of airflow and dust dispersion under different conditions of radial airflow distribution and negative pressure dust control. The results indicated that: ① Radial airflow distribution primarily affected the entrainment effect of the axial jet field, while negative pressure dust control flow mainly influenced the negative pressure effect of suction at the working face. When the ratio of radial airflow distribution to total air supply was not less than 0.8 and the ratio of total air supply to negative pressure dust control flow was less than 1.0, the air curtain transitioned to axial movement in the jet region, forming an axial dust control flow field with a thickness of not less than 1.4 m. ② As radial airflow distribution and negative pressure dust control flow increased, the airflow quantity and speed distribution on the suction side of the tunnel became more uniform, leading to reduced dust dispersion distance and lower dust mass concentration at the operator's position. Based on these findings, the optimized parameters for air curtain dust control in fully mechanized mining faces were determined: radial airflow distribution at 288 m³/min (with a ratio of radial airflow distribution to total air supply of 0.9) and negative pressure dust control flow at 426 m³/min (with a ratio of total air supply to negative pressure dust control flow of 0.75). Field measurements showed that after applying the optimized air curtain dust control parameters, the dust reduction rate at the operator's position reached 93.5%, significantly improving the working environment.